Massappo Wannua Tradition in Barru Regency: A Semiotic Study - Muhibuddin, Muhibuddin; Taufik, Muhammad (English Literature Studi Program Universitas Islam Makassar, 2025)
This research analyzes the Massappo Wanua tradition in Lapao Hamlet, Binuang Village, Barru Regency, using a semiotic approach. This tradition, which is performed annually by the Bugis community, aims to protect the village from disasters and maintain the balance between humans and nature. This research explores the symbols used in the ritual as well as the meaning of each symbol related to spiritual, social, and ecological values. The research method used is qualitative with data collection techniques in the form of participatory observation, interviews, and documentation. The results of the research using the theory of Charles Sander Pierce's Semiotics show that symbols such as rekkko ota, addupa-dupaang, and benno not only function ritually, but also reflect values such as welfare, honesty, and harmonious relationships between humans, nature, and spirituality. The findings enrich the understanding of Bugis people's cosmological relationship with nature and the ecological relevance of cultural practices that are preserved for generations.